Pengaruh Penjualan Bersih dan Beban Operasional Terhadap Laba Bersih Pada PT. Unilever Indonesia Tbk - Muhammad Fadhil; Sri Rani Fauziah; Devi Mulia Sari; Fahri Miraza (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
If the net sale of a business entity is more than its operating burden, the company shall record its net profit; but if its net sale is less than that of the company, it shall suffer a loss. This research aims to determine the effect of net sales on net profit at PT. Unilever Indonesia Tbk. To determine the effect of operational expenses on net profit at PT. Unilever Indonesia Tbk. To determine the effect of net sales and operational expenses on net profit at PT. Unilever Indonesia Tbk. This research uses quantitative research methods. The data collection technique is documentation. The data analysis technique in this research is to use multiple linear regression analysis. The research results show that net sales partially have a positive and insignificant effect on net profit at PT. Unilever Indonesia Tbk. Operational expenses partially have a negative and insignificant effect on net profit at PT. Unilever Indonesia Tbk. Net sales and operational expenses simultaneously influence on net profit at PT. Unilever Indonesia Tbk but insignificant